1972
DOI: 10.1111/j.1432-1033.1972.tb01816.x
|View full text |Cite
|
Sign up to set email alerts
|

A New Polynucleotide Complex Poly(s2C) · poly(I)

Abstract: Poly(s2C) -poly(1) complex formation (where s2C = 2-thiocytidylate) was shown by spectrophotometric titration, absorption-difference spectroscopy and hydroxyl-ion titration. The absorption temperature profile of the complex does not display a transition between 10 and 100 "C. Cooperative melting with a transition midpoint at 77 "C was observed only after destabilisation by 30°/, ethyleneglycol. A stabilizing effect of s2CMP residues in helices is further shown by the observation that 2501, sWMP in poly(C,,s2C)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1973
1973
1977
1977

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…The polarizable thioketo-groups of s~UMP, s2UMP or s2s4UMP will certainly effectively participate in dipole-induced dipole interactions if they are in appropriate positions. Recently we reported the physical properties of a new polynucleotide complex poly(s2C) -poly(1) [12]. The vertical interactions of sequent 2-thiocytosine bases stabilize the complex to such a degree, that its thermal denaturation in the absence of organic solvents cannot be achieved.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The polarizable thioketo-groups of s~UMP, s2UMP or s2s4UMP will certainly effectively participate in dipole-induced dipole interactions if they are in appropriate positions. Recently we reported the physical properties of a new polynucleotide complex poly(s2C) -poly(1) [12]. The vertical interactions of sequent 2-thiocytosine bases stabilize the complex to such a degree, that its thermal denaturation in the absence of organic solvents cannot be achieved.…”
Section: Discussionmentioning
confidence: 99%
“…The spectrophotometric equipment and methods employed in the following experiments have been described in previous papers [9,11,12]. The experimental details of sedimentation velocity analysis have also been reported elsewhere [9,12].…”
Section: Physical Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to specifications given, s20,w values were 10-15; 8-13; >10; 'v10 and >8 S, respectively. Poly(I).poly(s C) was prepared by spectrophotometric titration (3). A single lot with s = 20,w 14.1 was used for all animal experiments.…”
Section: Methodsmentioning
confidence: 99%
“…The ability of thiopyrimidine residues to stabilize the secondary structure of polynucleotides has been attributed to enhanced base-stacking interactions induced by the sulfur substituents (Faerber, Scheit & Sommer, 1972;Scheit & Gaertner, 1969;Bahr, Faerber & Scheit, 1973). Recent reviews have suggested that the bases in crystal structures of thiopyrimidines generally exhibit characteristic stacking patterns that involve intimate contacts between the sulfur substituent of one base and the ring systems of neighboring bases (Saenger, 1973;Saenger & Suck, 1973).…”
Section: Introductionmentioning
confidence: 99%